METANDAN MEZOG’OVAKLI UGLEROD OLISH REAKSIYASI TEZLIGIGA TURLI OMILLARNING TA’SIRI - Mamirzayev , Mashrab (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
. The rate of formation of nanocarbon layers in the presence of 15%Ni*5%Co*5%Fe*5%Cu/YuKS and 15%Ni*5%Co*5%Fe*5%Cu*2%Mo/YuKS catalysts the effect of different parameters of catalytic pyrolysis of methane (catalyst layer thickness, gas phase movement speed, process temperatures) was studied.